1991
DOI: 10.2307/1941551
|View full text |Cite
|
Sign up to set email alerts
|

Conditions for a Species to Gain Advantage from the Presence of Competitors

Abstract: The interaction between two species is usually assigned as though they were in isolation from all other species. Here we use a (known) method that determines species interactions more realistically, within the framework of the community to which they belong. This "inverse" method evaluates all the effects that one species experiences from another, both direct and indirect. We use this method to study the classical (though highly controversial) "competition community," where each species is considered (in the "… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
91
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(93 citation statements)
references
References 12 publications
1
91
1
Order By: Relevance
“…Ecologists have long appreciated that resource competitors can indirectly benefit one another via the suppression of shared competitors (22,23). And more recent studies have demonstrated that intransitivity in competitive networks can maintain diversity (9,10,11,15).…”
Section: Discussionmentioning
confidence: 99%
“…Ecologists have long appreciated that resource competitors can indirectly benefit one another via the suppression of shared competitors (22,23). And more recent studies have demonstrated that intransitivity in competitive networks can maintain diversity (9,10,11,15).…”
Section: Discussionmentioning
confidence: 99%
“…Indirect effects may be especially common in diverse communities, as the number of possible indirect effects increases exponentially with the number of species in a community (Abrams 1992), and can have important fitness consequences (Walsh 2013). In many cases, the magnitude of indirect ecological effects is greater than that of direct effects on species abundances, species coexistence, and community diversity (Vandermeer 1969, Stone and Roberts 1991, Lawler 1993, Miller 1994, Menge 1995. Although the ecological implications of indirect effects have been well studied, the evolutionary consequences have only recently gained attention (Walsh 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Other research suggests that species-specificity in plant-plant interactions may develop as plants interact simultaneously via competition for resources, facilitation, and allelopathy (Bertness 1991;Callaway et al 1991;Callaway 1994Callaway , 1995Holzapfel and Mahall 1999;Pugnaire 2002). Species-specific interactions may be produced by different combinations of positive and negative mechanisms, and by variation in the strength and direction of these interactions (Stone and Roberts 1991;Miller 1994;Callaway 1998;Berlow 1999;Levine 1999).…”
Section: Introductionmentioning
confidence: 99%